A Reflection on Public Policy Exception in Private International Law under the New York Convention, European Union Instruments and Ethiopian Law - Mogos, Abiyot (Bahir Dar University Journal of Law, 2023)
With the advent of globalization, an expansive increase in cross border transaction and socio-economic interaction has resulted in cross border law, judgment, and conflict of jurisdiction. This resulted in the development of private international law to ensure decisional harmony. Yet as a complete uniformity may sometimes run against public policy of concerned states, public policy exception is usually inserted. This piece reflects on the notion of public policy exception in private international law under the Ethiopian private international law rules in light of the European Union (EU) instruments and New York convention, and demonstrates how the EU experience could be helpful to improve the Ethiopian draft laws on the issue. Unlike EU, Ethiopia does not have comprehensive and binding laws of private international law other than some insufficient provisions under the civil procedure code (CPC) and the draft law. Even more, the existing Ethiopian rules under the CPC and draft law are crafted in manner that allow broader space to public policy exception including morality, are anti-foreign law or judgment in principle, less coherent and incomplete, and hence, are not as good as its EU counter parts to achieve the desired goal of private international law. Even if Ethiopia ratified the New York Convention, the scope of the Convention is limited to recognition and enforcement of award only. Hence, to have a complete and coherent Ethiopian legal regime on private international law, it is necessary to include pertinent stipulations on public policy exception under the EU instruments in the Draft proclamation.